2017
DOI: 10.1016/j.gexplo.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar amendments on As and Pb mobility and phytoavailability in contaminated mine technosols phytoremediated by Salix

Abstract: To cite this version:Manhattan Lebrun, Carmelo Macri, Florie Miard, Nour Hattab-Hambli, Mikael Motelica-Heino, et al.. Effect of biochar amendments on As and Pb mobility and phytoavailability in contaminated mine technosols phytoremediated by Salix. Journal of Geochemical Exploration, Elsevier, 2017Elsevier, , 182, pp.149-156. <10.1016Elsevier, /j.gexplo.2016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 44 publications
(43 reference statements)
5
46
0
1
Order By: Relevance
“…Application of biochar can also increase pH and enhance the physical properties of soil by raising its porosity and thereby its water holding capacity (Carlson et al 2015). Studies suggest that biochar has the potential to affect the behaviour of metals in the soil by altering their availability, solubility, transport and spatial distribution (Barrow 2012;Lebrun et al 2017), thereby immobilizing heavy metals and reducing uptake by plants (Fellet et al 2011;Karami et al 2011;Park et al 2011;Lomaglio et al 2017). The overall objective of the physical method is to reduce erosion and soil compaction while improving soil quality, thereby creating conditions suitable for re-vegetation of mine wastelands or their conversion into other productive land uses.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Application of biochar can also increase pH and enhance the physical properties of soil by raising its porosity and thereby its water holding capacity (Carlson et al 2015). Studies suggest that biochar has the potential to affect the behaviour of metals in the soil by altering their availability, solubility, transport and spatial distribution (Barrow 2012;Lebrun et al 2017), thereby immobilizing heavy metals and reducing uptake by plants (Fellet et al 2011;Karami et al 2011;Park et al 2011;Lomaglio et al 2017). The overall objective of the physical method is to reduce erosion and soil compaction while improving soil quality, thereby creating conditions suitable for re-vegetation of mine wastelands or their conversion into other productive land uses.…”
Section: Physical Methodsmentioning
confidence: 99%
“…According to earlier findings, biochar could improve the HM uptake by plants through growth increment [3,[20][21] or absorption of HM and reducing their bioavailability [22]. Regarding biochar-assisted phytoremediation with willow, Lebrun et al [23] showed that adding pinewood biochar to Pb-and As-contaminated soil increased the growth and biomass production of willow and the metal content in willow trees. In addition, a positive effect of biochar was noticed on soil quality [23].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biochar-assisted phytoremediation with willow, Lebrun et al [23] showed that adding pinewood biochar to Pb-and As-contaminated soil increased the growth and biomass production of willow and the metal content in willow trees. In addition, a positive effect of biochar was noticed on soil quality [23]. In contrast, Lebrun et al [6] found no positive effect after the addition of pinewood biochar on willow growth parameters and on the physicochemical properties in a multi-contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…The phyto‐availability of metals in soils depends on the metal(loid) species and their distribution between the solid phase and the pore water due to the soil physico‐chemical characteristics. Thus, many studies have been carried out on polluted soil to evaluate metal(loid) phyto‐availability . Moreover, a wide range of individual and sequential extraction schemes have been designed to evaluate the different forms of metal binding in soils using neutral salts (CaCl 2 and NH 4 NO 3 )…”
Section: Introductionmentioning
confidence: 99%